Antihyperlipidemic and hepatoprotective effect of zingiber cassumunar rhizome extract in high-fat diet-induced hyperlipidemic rats: the role of antioxidant activity - Mahfudh, Nurkhasanah; Sulistyani, Nanik; Sari, Novita; Sari, Indah Puspati; Adrian, Dedi; Fezah Othman,; Zainul Amiruddin Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Hyperlipidemia and oxidative stress are major risk factors for the onset of cardiovascular diseases, and the oxidative stress caused by high level of lipids can cause liver damage. Zingiber cassumunar has been reported to contain a high antioxidant content that may provide therapeutic advantages. The present study was to evaluate the antihyperlipidemic and hepatoprotective effects of Z. cassumunar rhizome extract (ZCRE) in high-fat diet (HFD)-induced hyperlipidemic rats model and investigate the mechanism through its effect on the endogenous antioxidant enzymes. In this study, the rhizomes of Z. cassumunar was extracted using ethanol 96% (v/v) and evaporated to get the concentrated Z. cassumunar rhizome extract (ZCRE). Thin layer chromatography (TLC)-densitometry was performed to determine the curcumin content in the extract. High fat diet-induced hyperlipidemia model was used to evaluate the anti-hyperlipidemic and hepatoprotective activities of ZCRE in rats. Male Wistar rats were randomly divided into five groups: normal control; High fat diet-induced hyperlipidemic rats (HFD); High Fat Diet and 100 mg/kgBW of ZCRE (HFD + 100 mg/ kgBW); High Fat Diet and 200 mg/kgBW of ZCRE (HFD + 200 mg/kgBW); and High Fat Diet and 400 mg/kgBW of ZCRE (HFD + 400 mg/kgBW). The antihyperlipidemic and hepatoprotective potential of ZCRE were assessed through a series of analyses of body weight, blood biochemical parameters, which include total cholesterol (TC), triglycerides (TG), the serum glutamic-oxaloacetic transaminase (SGOT) and serum glutamic-pyruvic transaminase (SGPT). The antioxidant activity of catalase (CAT) and glutation peroxidase (GSH-Px) were assessed on the liver homogenate. Data of the study were presented as mean ± SD and analyzed by using one way analysis of variance (ANOVA) followed by Least Significant Difference (LSD) test for multiple comparisons. The TLC analysis showed that ZCRE contained a significant amount of Curcumin. In addition, the study has also shown that ZRCE was able to significantly lower the levels of total cholesterol, triglyceride, SGPT, and SGOT as compared to hyperlipidemic rats (p<0.05) Concomitantly, the activity of CAT and GSH-Px was found significantly increased (p<0.05) when compared to hyperlipidemic control, with the dose of 400 mg/kg BW being the most effective. This study showed the significant antihyperlipidemic and hepatoprotective effects of ZCRE in HFD-induced hyperlipidemic rats, which mechanism might possibly connect to the increased antioxidant enzyme activities.